Sosialisasi Peningkatan Kesadaran Orang Tua Tentang Pencegahan Pernikahan Usia Dini di Kelurahan Wonoasih Probolinggo: Sosialisasi Peningkatan Kesadaran Orang Tua Tentang Pencegahan Pernikahan Usia Dini di Kelurahan Wonoasih ProbolinggoEarly marriage remains a significant social issue in Indonesia, including in Wonoasih Village, Probolinggo City. Low parental awareness of the negative impacts of early marriage is a major contributing factor to its persistence. This community service research emp - Moh Husnan; Mardiana; Zahroil Warda; Aisyah Bashiratul Mahiroh; M. Nabat Ardli; lailatul chasifah (LPPI UMN AL WASHLIYAH, 2025)
Early marriage remains a significant social issue in Indonesia, including in Wonoasih Village, Probolinggo City. Low parental awareness of the negative impacts of early marriage is a major contributing factor to its persistence. This community service research employed the Participatory Action Research (PAR) method to enhance parents’ understanding and awareness of the importance of preventing early marriage. The activities were conducted through preparation, interactive socialization, and evaluation stages using pre-test and post-test assessments. Results indicated a significant increase in parental knowledge and a positive shift in attitudes supporting the postponement of marriage until children reach maturity. Despite cultural resistance challenges, the participatory approach proved effective in empowering parents as agents of change within the community. These findings suggest the need for sustained socialization programs involving local stakeholders to effectively reduce the incidence of early marriage.